European Academy of Cancer Sciences – position paper. Issue 11 (21st September 2018) - Adami, Hans‐Olov; Berns, Anton; Celis, Julio E.; de Vries, Elisabeth; Eggermont, Alexander; Harris, Adrian; zur Hausen, Harald; Pelicci, Pier Giuseppe; Ringborg, Ulrik
Abstract : The European Academy of Cancer Sciences (EACS) is an independent advisory body of well‐recognised medical specialists and researchers striving to create a compelling interactive continuum of cancer research, from innovative basic research to implementation of state‐of‐the‐art evidence‐based cancer care and prevention. Achieving the above will entail bridging high‐quality basic and preclinical cancer research to research on prevention, early detection and therapeutics as well as improving coordination of translational research efforts across Europe. The latter is expected to be expedited through quality assuring translational cancer research in Comprehensive Cancer Centres – entities that link research with the healthcare system – and networks of cancer research centres. Achieving a critical mass of expertise, resources and patients is crucial. Improving late translational research, which involves clinical studies to assess effectiveness, and added value for the health care is also a high priority. Both high‐quality Big Data collections and the intelligent use of these data will promote innovation in cancer research and support outcomes research to assess clinical utility, quality of cancer care and long‐term follow‐up of treated patients. The EACS supports the mission‐oriented approach recently proposed by the European Commission in Horizon Europe to deal with major challenges and would like to persuade the EU and its member states to formally launch a mission in cancer to boost and streamline the cancer research continuum in Europe. Building a coherent translational cancer research continuum with a focus on patients and individuals at risk will require, however, foresight as well as the extensive and continuous provision of evidence‐based advice to inform policy. Abstract : The European Academy of Cancer Sciences (EACS), an independent advisory body of medical specialists and researchers, has issued a position paper encouraging the European Union and its member states to formally launch a mission to boost and streamline cancer research.